A five years study on drug-related deaths in Campania (Italy) - Renata Borriello; Anna Carfora; Paola Cassandro; Raffaella Petrella (Istituto Superiore di Sanità, 2014)
OBJECTIVES: The study regards n. 267 drug related deaths submitted to toxicological analyses for forensic purpose, since 2008 to 2012, at the Laboratory of Forensic Toxicology of the Second University of Napoli (SUN), Italy. Among the cases studied (94% males and 6% females) the 13.1% regards foreign citizens. METHODS: For each case autopsy findings and all drugs detected were recorded. In addition other epidemiological data such as age, race, gender, place and circumstance of death were also supplied. A systematic toxicological analysis (STA) for illicit drug, other pharmaceuticals, new psychotropic substances and ethanol has been applied on the specimens collected at autopsy and all positive results were confirmed by a quantitative analysis (GC/MS or LC-MS/MS). RESULTS: Toxicological results shows that simultaneous use of multiple illicit drugs was responsible of the largest mortality rate (57.7%), in both males and females. In the poly-drug use the cocaine was the most detected substance. The association of heroin/cocaine was identified in the 22.5% of deaths. The finding of only one drug was correlated with an opiate drug for the 14.2% and with cocaine for the 4.5% of cases. The distribution by age and gender demonstrates an increase in deaths among males aged over 30 years and among women older than 35 years. The territorial distribution of the deaths in the different surrounding areas and in the residential quarters of the Naples city demonstrates that the 76% of deaths occurred in a place different from the usual residence. CONCLUSION: Results obtained demonstrate that prevails, at present, the need to specifically explore the changing patterns of poly-drug use among addicts, because studying the prevalence of mortality subsequent to the consumption of a single illicit drug may be insufficient to guide preventive policies in public health.